1996
DOI: 10.3177/jnsv.42.1
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Serum Ascorbic Acid Concentrations in Patients with Diabetic Macroangiopathy.

Abstract: SummaryThe relationship between serum ascorbic acid (AA) and diabetic macroangiopathy was studied. Fifty-six patients with non insulin-dependent diabetes mellitus were examined, together with 20 healthy controls matched for age against the diabetes patients. Aortic pulse wave velocity (PWV) was taken as an index of the severity of ather osclerosis. The level of serum AA in diabetic patients was significantly lower than that of the controls. Among the diabetic groups, those with elevated PWV levels by age demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Ineffective recruitment of GLUT4 to the cell surface results in excessive glucose accumulation in the blood and type II diabetes clinically. In addition to aberrant glucose metabolism, some evidence suggests that diabetics may also have decreased cellular concentrations of ascorbate or increased requirements for it (14)(15)(16)(17). Considering the importance of GLUT4 in glucose uptake and its possible implications in ascorbate metabolism, it was worthwhile to pursue investigation of DHA transport by GLUT4.…”
Section: Introductionmentioning
confidence: 99%
“…Ineffective recruitment of GLUT4 to the cell surface results in excessive glucose accumulation in the blood and type II diabetes clinically. In addition to aberrant glucose metabolism, some evidence suggests that diabetics may also have decreased cellular concentrations of ascorbate or increased requirements for it (14)(15)(16)(17). Considering the importance of GLUT4 in glucose uptake and its possible implications in ascorbate metabolism, it was worthwhile to pursue investigation of DHA transport by GLUT4.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that the blood AsA level is signifi cantly lower in diabetic patients compared to control subjects and no signifi cant differences are observed in the serum DAsA level between patients and controls (Nagano et al 1996 ).…”
Section: Diabetes In Human Subjectsmentioning
confidence: 98%